2007
DOI: 10.1002/ajp.20460
|View full text |Cite
|
Sign up to set email alerts
|

Male parenting and response to infant stimuli in the common marmoset (Callithrix jacchus)

Abstract: Callithrix jacchus infants are raised in complex family environments where most members participate in rearing the young. Many studies examining male parental behavior have focused on the carrying of infants with observations made within the family context. However, interference from family members can make it difficult to assess the father's motivation to care for infants. Our goals were to develop a testing paradigm for determining an individual's response to infant stimuli separate from family influences, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 52 publications
(43 reference statements)
1
59
0
Order By: Relevance
“…2). 32,35 Zahed and coworkers 36 demonstrated that adult male marmosets in general possess a spontaneous motivation to care for any infant, related or not. Helpers often provision offspring by giving food calls and actively offering high-value food items rather than in response to infant begging.…”
Section: Box 1: Spontaneous Prosociality In Nonhuman Primatesmentioning
confidence: 99%
“…2). 32,35 Zahed and coworkers 36 demonstrated that adult male marmosets in general possess a spontaneous motivation to care for any infant, related or not. Helpers often provision offspring by giving food calls and actively offering high-value food items rather than in response to infant begging.…”
Section: Box 1: Spontaneous Prosociality In Nonhuman Primatesmentioning
confidence: 99%
“…Many studies have therefore used the marmoset for comparative morphology to investigate neurocircuitry or neuroanatomy (Roberts and Wallis, 2000;Bourne et al, 2007;Karasawa et al, 2007;Pinato et al, 2007). The marmoset has been used to study behavior, ranging from the psychobiological features of anxiety and fear (Barros and Tomaz, 2002) to sexual behavior (Dixson, 2001), social interactions (Ziegler and Sousa, 2002;Caldwell and Whiten, 2004;Schiel and Huber, 2006), and parental care (Da Silva Mota et al, 2006;Dettling et al, 2007;Zahed et al, 2008). Behavioral testing in marmosets can be also used to test higher-order processing of cortical functions using more complex cognitive tasks than in rodents.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence in primates suggests that males will care for unrelated as well as related infants in some cases. Experiments with common marmosets (Callithrix jacchus) showed that males removed from the context of other adults exhibited similar interest in caring for related and unrelated infants (Zahed et al 2008). In a 12-month study of alloparental behavior in Mahale chimpanzees, Nishida (1983) reported such behavior performed by an adolescent male that was not maternally related to the infants he carried and groomed with, similar to what is normally seen in young female chimpanzees.…”
Section: Discussionmentioning
confidence: 77%